โปรแกรมเสริมสร้างสมรรถนะครูด้านการจัดการเรียนรู้โดยใช้ GOOGLE CLASSROOM ในโรงเรียน สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาขอนแก่น เขต 5 - สมมาสี, สุวรรณี; กลิ่นกุหลาบ, ไพโรจน์ (วารสารพุทธปรัชญาวิวัฒน์, 2025)
บทความวิจัยนี้เป็นการวิจัยแบบผสมวิธี มีวัตถุประสงค์เพื่อ 1) ศึกษาสภาพปัจจุบัน สภาพที่พึงประสงค์ ความต้องการจำเป็น และแนวทางการเสริมสร้างสมรรถนะครูด้านการจัดการเรียนรู้โดยใช้ Google Classroomในโรงเรียน สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาขอนแก่น เขต 5  กลุ่มตัวอย่าง ได้แก่ ครู จำนวน 322 คน ได้มาโดยการสุ่มแบบแบ่งชั้น และกลุ่มผู้ให้ข้อมูล 3 โรงเรียน 6 คน การเลือกแบบเจาะจง เครื่องมือที่ใช้ ได้แก่ แบบสอบถาม และแบบสัมภาษณ์แบบกึ่งโครงสร้าง 2) สร้าง ตรวจสอบยืนยัน และประเมินความเหมาะสม ความเป็นไปได้ ความเป็นประโยชน์ของโปรแกรมฯ จากผู้ทรงคุณวุฒิ จำนวน 5 คน ผ่านการสนทนากลุ่ม และประเมินความเหมาะสม ความเป็นไปได้ ความเป็นประโยชน์ โดยผู้มีส่วนได้ส่วนเสีย จำนวน 15 คน การเลือกแบบเจาะจง เครื่องมือที่ใช้ แบบบันทึกการสนทนากลุ่ม และแบบประเมิน สถิติที่ใช้ ได้แก่ ค่าร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน ค่าความเที่ยงของเนื้อหา ค่าอำนาจจำแนก ค่าความเชื่อมั่น และความต้องการจำเป็น ผลการวิจัยพบว่า 1) สภาพปัจจุบัน โดยภาพรวมอยู่ในระดับปานกลาง และสภาพที่พึงประสงค์ โดยภาพรวมอยู่ในระดับมาก ความต้องการจำเป็นเรียงลำดับความสำคัญของความต้องการจำเป็นจากมากไปหาน้อย ได้แก่ ด้านการสร้างชั้นเรียนด้วย Google Classroom ด้านการจัดการเนื้อหาด้วย Google Classroom ด้านการวัดและประเมินผลผ่าน Google Classroom และด้านความรู้ความเข้าใจเกี่ยวกับการใช้ Google Classroom ตามลำดับ 2) ผลการสร้าง ตรวจสอบยืนยันโปรแกรมเสริมสร้างสมรรถนะครูด้านการจัดการเรียนรู้โดยใช้ Google Classroom มี 5 องค์ประกอบดังนี้ 1) หลักการ 2) วัตถุประสงค์ 3) เนื้อหา 4) วิธีการพัฒนา และ 5) การประเมินผล และผลการประเมินความเหมาะสม ความเป็นไปได้ และความเป็นประโยชน์ โดยรวมอยู่ในระดับมากที่สุด This research study employs a mixed-methods approach with the following objectives: 1) to examine the current state, the desired state, essential needs, and strategies for enhancing teachers' competencies in instructional management using Google Classroom in schools under the jurisdiction of the Khonkaen Primary Educational Service Area Office 5. The sample consisted of 322 teachers selected through stratified random sampling, while qualitative data were collected from six key informants across three schools, chosen through purposive sampling. The research instruments included a questionnaire and a semi-structured interview. 2) To develop, validate, and assess the feasibility, appropriateness, and usefulness of the competency enhancement program, five experts participated in a focus group discussion for validation, and 15 stakeholders evaluated the program’s suitability, feasibility, and benefits through purposive sampling. The instruments utilized included a focus group discussion record and an evaluation form. The statistical methods applied in the study comprised percentage, mean, standard deviation, content validity index, item discrimination, reliability coefficient, and need assessment analysis. The research findings revealed that: 1) the overall current state of teachers' competencies in using Google Classroom was at a moderate level, while the desired state was at a high level. The prioritized essential needs, ranked from highest to lowest, included: (1) creating a virtual classroom using Google Classroom, (2) managing instructional content via Google Classroom, (3) assessing and evaluating student performance through Google Classroom, and (d) acquiring fundamental knowledge and understanding of Google Classroom. 2) The development and validation of the competency enhancement program resulted in five key components: (1) principles, (2) objectives, (3) content, (4) development methods, and (5) evaluation. The overall assessment of the program's appropriateness, feasibility, and usefulness was rated at the highest level.